Mysticete migration revisited: are Mediterranean fin whales an anomaly?. (3rd May 2016) - Geijer, Christina K.A.; Notarbartolo di Sciara, Giuseppe; Panigada, Simone
Abstract: The generally accepted model of Mysticete whale migration is that most individuals undertake seasonal migrations between high and low latitudes. Although numerous exceptions have been described in the literature, the traditional model remains unexamined. This paper represents the first 'official' challenge to the traditional model of Mysticete migration. We set out to review the current state of knowledge on the Mediterranean fin whale migratory pattern, and to examine whether the small, resident population in the Mediterranean is an anomaly within the framework of the traditional model of Mysticete migration. We investigated the prevalence of alternative migratory strategies among the Mysticete whales, reviewing the migratory habits of the Mediterranean fin whales and those of other fin whale and baleen whale populations. We reach three main conclusions. First, the seasonal behaviour of the resident Mediterranean fin whales is highly dynamic, and a decade of research has not clarified prevailing uncertainties regarding migration patterns. Second, migration strategies similar to those observed in the Mediterranean fin whales are commonly seen in other populations of baleen whales. Third, the traditional model of whale migration is too simplified to describe the repertoire of Mysticete migratory behaviours accurately. We argue that the paradigm of baleen whale migration warrants further scrutiny to account for more complex movement strategies. We suggest that Mysticete migration should be thought of as a continuum of different strategies that have evolved in the face of different selective pressures. Instead of representing an exception to the rule, the resident Mediterranean fin whales may in fact fall towards one end of a larger spectrum of migratory behaviours. A greater knowledge of ecological factors, reproductive patterns, and local adaptations will be needed to understand the evolutionary mechanisms behind the diversity of migratory habits.